Performance of a dental surgeon against the COVID-19 pandemic in primary health care: experience report (Research, Society and Development, 2023)
In the face of a public health emergency, such as the COVID-19 pandemic, health services were tasked with reorganizing themselves, and the multidisciplinary exercise was the promoter of health actions in Primary Health Care. active at this level of care, the essential role of the dental surgeon as an actor in coping with the aforementioned disease is highlighted. In this perspective, this article is a descriptive study, in the experience report modality, linked to the municipality of Bahia, in period between March and June 2020. The study was prepared based on changes in the flow of care at a family health unit, focusing on the performance of the Dentistry nucleus. With the reorganization of the service, there was a greater adherence of the population to the recommendations of the health team, observed in the demarcation of the flow of individuals that showed good results, reducing the risk of viral transmission between patients and health professionals. And for the effectiveness of the measures, changes were necessary in the flows, continuous updates, reinforcement in biosecurity, as well as changes in dental care. Based on this experience, the importance of teamwork in the consolidation of humanized and comprehensive care is highlighted, with emphasis on the protagonist role of the dentist in the aforementioned sanitary context, in Primary Health Care.